Potentialities of adjuvant endocrine therapy for breast cancer (Part II) - N. Yu. Dobrovolskaya; E. K. Vvoznyi; Yu. M. Bychkov (Опухоли женской репродуктивной системы)
Potentialities of adjuvant endocrine therapy for breast cancer (Part II)